The boy next door [videorecording (DVD)] - Cohen, Rob, 1949-; Lopez, Jennifer, 1970-; Guzman, Ryan, 1987-; Chenoweth, Kristin (Universal Studios, 2015)
Jennifer Lopez stars as Claire Peterson, a high school literature teacher struggling to get back in the dating game after separating from her cheating husband. When handsome and charismatic nineteen year old Noah moves in next door, Claire has a moment of weakness that leads to an extremely intense and intimate night together. Noah's attraction quickly turns into a dangerous, violent obsession, forcing Claire to her limits as she protects her world from being torn apart.